The Effectiveness of Social Media in Learning English: A Systematic Review - Ardiel, Vonny (Vivid: Journal of Language and Literature, 2024)
The author conducted a systematic review of the published literature on the use of social media in learning English to answer two questions. These research questions are (1) How do the results of the intervention using social media affect learning achievement and outcomes such as learning motivation, interest, understanding, attitudes and skills for English language learners? (2) What are the obstacles and benefits of implementing social media by teachers? This study uses a systematic review method with the PICO technique in searching for articles to be reviewed. Reviews were written according to Preferred Reporting Items for Systematic Reporting and Meta-Analysis (PRISMA). The author also uses the Publish or Perish application and VOSviewer to determine research gaps. The author is looking for articles that discuss social media interventions in learning English as a foreign language. The results obtained were fourteen pieces of literature that met the inclusion criteria. Interventions that use social media are associated with the effectiveness and success of achieving learning outcomes (test scores) and English language skills, and attitudes (cooperation, collaborative and cooperative). The conclusion is that social media interventions in learning English can improve students’ language skills as seen in the form of values, skills, motivational attitudes, self-confidence, ability to communicate and collaborate, critical thinking and self-efficacy in English. Benefits for teachers, social media can help promote teaching, motivate students, support and build teaching.